Nature, environment, and society - Sutton, Philip W. (Houndmills, Basingstoke, Hampshire ; New York : Palgrave Macmillan, 2004)
Tracing the origins and development of environmental groups and issues, this is a critical review of the most significant debates in environmental sociology. It covers topics such as movements, ideas and theories, green consumerism, sustainable development and ecological moderisation.
Includes bibliographical references and index.
Keywords: Human ecology -- Philosophy; Deep ecology -- Philosophy; Sociology -- Philosophy; Nature -- Effect of human beings on; Gaia hypothesis; Environmental responsibility; Environmental ethics